Reaction Mechanism for the Formation of Dialkylated Nickel(II) Salen Involved in the Catalytic Reduction of (Bromomethyl)cyclopropane. Issue 14 (12th November 2016) - Lambert, Clayton L.; Enters, Mikaela E.; Rastogi, Shiva K.; Brown, Christopher T.; Shoulders, Ben A.; Brittain, William J.; Ji, Chang
Abstract : Cyclic voltammetry (CV) and controlled-potential electrolysis (CPE) were employed to examine the reaction between electrogenerated ligand-reduced nickel(II) salen and (bromomethyl)cyclopropane. Cyclic voltammograms for nickel(II) salen in the presence of (bromomethyl)cyclopropane exhibit characteristic features for the catalytic reduction of the substrate. Bulk electrolyses of (bromomethyl)cyclopropane at carbon cathodes in dimethylformamide catalyzed by nickel(II) salen were carried out to investigate the mechanism for the formation of dialkylated nickel(II) salen, which was analyzed and identified by high-performance liquid chromatography (HPLC). The corresponding dialkylated nickel(II) salen was further purified and collected by preparative-scale HPLC. Its complete structure was revealed by electrospray-ionization mass spectrometry (ESI-MS), 1 H NMR, COSY, and HECTOR NMR spectrometry. The clear-cut reaction mechanism for its formation was proposed on the basis of current and previous studies.